The Australian Income Tax - Copland, D. B. (Quarterly Journal of Economics, 1924)
Growing Importance of Tax Problems. The Australian Commission. — State and Federal Taxes, 72. — The Income Tax, 74. — The Averaging System, 76. — Exemptions and Allowances, 80. — Taxation at the Source, 83. — Differentiation, 88. — Graduation, 89. — Miscellaneous Topics, 91.